A First Principles Investigation of Mercuric Iodide: Bulk Properties and Intrinsic Defects - F. Ayres (Brazilian Journal of Physics, 2004)
We carried a theoretical investigation on the properties of mercuric iodide in the red tetragonal crystallinephase, and its respective intrinsic defects. Our calculations were performed using the ab initio spin-polarizedfull-potential linearized augmented plane wave method, and taking into account full atomic relaxation. Theresults on the structural, electronic, and optical properties were compared to available experimental data.